Multi-material printing of PVDF composites: A customized solution for maintenance of heritage structures. (March 2023) - Kumar, Vinay; Singh, Rupinder; Ahuja, Inderpreet Singh
In the past three decades, 3D printing technologies have emerged as a convenient tool for the repair and maintenance of heritage structures. But hitherto little has been reported on multi-material 3D printed composites with 4D properties for the repair and maintenance of heritage structures. The present study reports the investigations on multi-material 3D printing of conducting and non-conducting polyvinylidene fluoride (PVDF) composite layers with self-actuating and self-healing properties to repair non-structural cracks in heritage buildings. The non-conducting (PVDF-CaCO3 ) and conducting (PVDF-graphene-Mn doped ZnO) composites were 3D printed and tested for electrostriction-based strain measurement for 4D analysis. The thermo-mechanical properties of the composite solution were obtained from dynamic mechanical analysis (DMA). The electrical, bonding, and morphological properties were investigated by current-voltage (I-V), x-ray diffraction (XRD), Fourier transformed infrared (FTIR), and scanning electron microscopy (SEM)-energy dispersive spectroscopy (EDS) analysis. Results of the self-elongation and contraction by electrostriction in PVDF composite demonstrate the feasibility of 3D printing technology as a novel tool to fabricate cost-effective smart solutions for the repair and maintenance of heritage structures.